A volcanic ash UTILIZATION OF THREE-BAND VOLCANIC ASH PRODUCT (TVAP) TO IDENTIFY THE DISTRIBUTION OF VOLCANIC ASH AT THE SINABUNG ERUPTION ON 8 AND 10 AUGUST 2020 - Siboro, May; Firmansyah, Andik (jurnal ATMOSPHERE, 2023)
One of the natural disasters that occur in the atmosphere is a volcanic eruption or what is known as an "eruption". The danger of volcanic eruptions can be in the form of hot clouds, ejected material (incandescent), heavy rain of ash, lava and lava floods. One of the active volcanoes and the highest mountain in North Sumatra is Mount Sinabung. Mount Sinabung is included in the category of strato volcano with an altitude of 2,460 meters above sea level and since the 2010 eruption has been classified as a type A mountain. Until now, Mount Sinabung still erupts frequently and releases harmful products for both human health and the environment, such as volcanic ash. This study aims to identify the distribution of volcanic ash resulting from the eruption of Mount Sinabung on August 8 and August 10 2020 by using an algorithm method, namely multispectral infrared or TVAP which utilizes three infrared channels with different wavelengths for each. Based on the analysis that has been carried out, it is found that the direction of distribution of volcanic ash is to the east and southeast of the location of Mount Sinabung. It can also be seen that there are meteorological elements, such as wind and rainfall that occur during an ongoing eruption which have a good impact by reducing the intensity of volcanic ash so that the volcanic ash column thins.